Formal Organizational Initiatives and its Impact on Employee Engagement - Thomas, Rejoice (International Journal of Psychosocial Rehabilitation, 2020)
Due to globalization and diversified manpower requirements, the business scenario has completely changed. Each and every organization, whatever the scale, is thinking of ways to change the business situation to accomplish competitive advancement in the market.